Gemination of maxillary incisors in decidous and permanent dentition – a case report - Isidora Nešković; Aleksandar Anđelković; Duška Blagojević; Sanja Vujkov; Jelena Komšić; Bojan Petrović (Биомедицинска истраживања, 2024)
Introduction: Shape variations of teeth can be present both in perma nent and in deciduous dentition. Gemination, fusion, concrescention, and ,,twin teeth" are development anomalies. Aim: of this article is to show different cases of simultaneous gemination in deciduous denti tion and supernumerary teeth in permanent dentition in upper incisors region. Case report. A nine-year-old girl, suffering from juvenile idiopathic arthritis, has been sent to the Dental Clinic of Vojvodina. The clinical examination and OPG (orthopantomography) analysis revealed the presence of supernumerary tooth in the region of tooth 51, and also supernumerary tooth in tooth region 11. There was the presence of a cyst in the region 23, which was corresponding to the follicular cyst. The treatment plan included extraction of tooth 51 and supernumer ary tooth, extraction of tooth 52, and control examination after three months with 3D radiography. Conclusion: Full cooperation between pediatric dentist, oral surgeon and orthodontics is required. Therapy should be focused on balanc ing the occlusion and gaining best aesthetic results. The significance of highlighting the importance of this case lies in its contribution to expanding our understanding of gemination anomalies in the dental f ield. By presenting a rare occurrence involving gemination of maxillary incisors in both deciduous and permanent dentition, this case report offers valuable insights into the clinical manifestations, diagnostic ap proaches and treatment strategies associated with this condition.
Keywords: twin teeth; pediatric dentistry; germination; variations